A novel phthalazine based highly selective chromogenic and fluorogenic chemosensor for Co2+ in semi-aqueous medium: application in cancer cell imaging. Issue 2 (10th December 2014) - Patil, Smita; Patil, Rahul; Fegade, Umesh; Bondhopadhyay, Banashree; Pete, Umesh; Sahoo, Suban K.; Singh, Narinder; Basu, Anupam; Bendre, Ratnamala; Kuwar, Anil
Abstract : A new phthalazine based chemosensor3 was developed for the detection of Co 2+ . Abstract : A new phthalazine based chemosensor3 was developed for the highly selective and sensitive detection of Co 2+ in the mixed solvent system, CH3 CN–H2 O (1 : 1, v/v). In the presence of Co 2+, the colour of the solution3 changed from yellow to green; the absorption maxima of3 was red-shifted from 383 nm to 435 nm, and the fluorescence of3 at 550 nm was significantly enhanced. The sensor3 showed a detection limit down to 25 nM by forming a complex species with Co 2+ in 1 : 1 stoichiometry. Furthermore, by means of confocal laser scanning microscopy experiments, it has demonstrated that it can be used as a fluorescent probe for monitoring Co 2+ in living cells.